Fotossíntese, crescimento e composição química em plantas de Theobroma cacao L. submetidas a diferentes concentrações de silicato de potássio e sua interação com insetos-praga - Pinto, Diego Guimaraes (2011)
The control of insect pests through the use of pesticides, is still the most method used in the cultivation of cocoa. However, due to environmental issues, there need to seek new alternatives of control less harmful the environment and to humans. In this context, silicon is a nutrient that is being used in various cultures, due to its beneficial effects on plant physiology and protection to the attack of insect pests and disease. The aim of this study was to evaluate the photosynthesis, growth and chemical composition in three cacao genotypes under different concentrations of potassium silicate and its interaction with insect pests. Two experiments were conducted, the first being installed under an agroforestry system comprising Bactris gasipaes and Theobroma cacao, in a randomized block design, with four replications, in a factorial 3 x 3, consisting of three genotypes (TSH 1188, CCN 51 and Catongo), three doses of potassium silicate (0, 3 and 6 mL L-1) applied to leaves. Were conducted evaluations of vegetative growth, of kinetics of fluorescence emission from chlorophyll a, of chlorophyll content, of incidence and degree of damage caused by insect pests, beyond from the silicon content in the leaves. The growth of cacao genotypes was reduced with the application of doses of potassium silicate, possibly due to the partition of assimilates that were being used in the biosynthesis of compounds involved in plant resistance to insects. The genotype TSH 1188 showed the highest increase in growth and dry matter compared to CCN 51 and Catongo, being the only genotype that showed the highest content of chlorophyll and improvement in parameters of chlorophyll fluorescence when applied to 3 mL L-1potassium silicate, mainly in the energy flow of photosystem II and the index of performance of the plant for absorption (PIABS) and total (PITOTAL). The application of potassium silicate at dose 6 mL L-1 significantly reduced the incidence and level of damage by insect pests in cocoa genotypes. However, did not have significant effect of the application of potassium silicate on the silicon content in the leaves of the genotypes of cacao studied in relation to the control. The second experiment was conducted in a greenhouse with the same treatments and statistical design of experiment previous. In it were evaluated gas exchange, foliar concentrations of soluble phenolic compounds total, the chlorophyll fluorescence a, besides a preference test with a chance of free choice with aphids. The highest rates of photosynthesis and stomatal conductance were found in TSH 1188 and CCN 51. These same genotypes showed higher index of performance (PIABS and PITOTAL), a result of increased density of centers reaction active of photosystem II (RC/ABS), quantum yield of PSII (fP0 / (1-fP0)) and efficiency of reactions redox beyond the quinone a-(?0/1-?0). The application of potassium silicate increased net photosynthesis, but did not affect the performance indices (PIABS and PITOTAL). The phenolic content increased in genotypes CCN 51 and Catongo, the preference of the aphid was reduced with application of 6 mL L-1 of potassium silicate only in TSH 10 1188. Due on the results from the two experiments, application of silicon is promising to increase the resistance of cacao insect pests, since it promotes the increase of photosynthetic activity and production of plant metabolites involved in defense mechanisms of the cacao tree.